High Concentrate Supplementation during Late Pregnancy and Lambing Reduced Mortality of Triplet-Bearing Maternal Ewes. - Haslin E; Blumer SE; Gordon D; Kearney GA; Kenyon PR; Kubeil LJ; Refshauge G; Trompf JP; Thompson AN (MDPI (Basel, Switzerland), 2024)
Low survival of triplet-bearing ewes and their lambs represents lost production and a welfare issue. The effects of feed-on-offer (FOO; low: 1205 vs. high: 1980 kg DM/ha) and concentrate supplementation (low: 50 vs. high: 300+ g/ewe/day) levels during late pregnancy and lambing on the survival of triplet-bearing ewes and their lambs were investigated on 10 commercial farms using 1772 triplet-bearing Maternal ewes. Ewe and lamb survival were estimated at marking, and ewe body condition score (BCS) was recorded in late pregnancy and at marking. Although FOO treatment had no effect on triplet-bearing ewe mortality, receiving higher supplementation decreased mortality by 40% and increased BCS at marking by 0.14 compared with a lower supplementation (p < 0.05). Supplementation, FOO treatments, weather conditions during lambing and shelter availability had no effect on triplet-lamb survival. These findings suggest no additional benefit to triplet-bearing ewe survival when FOO levels exceed 1200 kg DM/ha during late pregnancy and lambing, but increased supplementation can reduce ewe mortality. Further research is required to determine the response to the supplementation level at lower FOO levels on triplet-bearing Merino ewes and their lambs and establish whether supplementation of triplet-bearing ewes during late pregnancy and lambing with higher levels of concentrates would be cost-effective.
Keywords: ewe mortality; feed-on-offer; lamb survival; paddock topography; supplementary feeding; triplet-born lambs